Novel Highly Divergent SARS-CoV-2 Lineage With the Spike Substitutions L249S and E484K - Laiton-Donato, Katherine; Usme-Ciro, Jose A.; Franco-Muñoz, Carlos; Álvarez-Díaz, Diego A.; Ruiz-Moreno, Hector Alejandro; Reales-González, Jhonnatan; Prada, Diego Andrés; Corchuelo, Sheryll; Herrera-Sepúlveda, Maria T.; Naizaque, Julian; Santamaría, Gerardo; Wiesner, Magdalena; et al. (Frontiers in Medicine, 2021)
COVID-19 pandemics has led to genetic diversification of SARS-CoV-2 and the appearance of variants with potential impact in transmissibility and viral escape from acquired immunity. We report a new and highly divergent lineage containing 21 distinctive mutations (ten nonsynonymous, 8 synonymous and 3 substitutions in non-coding regions). The amino acid changes L249S and E484K located at the CTD and RBD of the Spike protein could be of special interest due to their potential biological role in the virus-host relationship. Further studies are required for monitoring the epidemiologic impact of this new lineage.